JUSTIFIKASI EKSTRAK TANAMAN LAMIACEAE SEBAGAI PROSPEK OBAT - Abdul Wahid; Jeklin Sampe; Emillia Rahayu; Darius Rupa; Zulfadli Zulfadli (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2020)
in the family Lamiaceae are very widely used by humans because these plants commonly contain aromatic compounds such as Rosmarinus Officianalis, Hyptis capitata etc. Various plants species that have been studied, especially plant extracts from the family Lamiaceae reveal the content of compounds and prospects for their benefits to humans. The results of a review of various studies revealed that the species of the family Lamiaceae generally has the potential as an antimicrobial, antidiabetic, antioxidant, anti-tumor, anti-immobility, anti-inflammatory, antifungal, Anti-Methicillin resistant Staphylococcus aureus, traditional medicine and the pharmaceutical industry etc. Compounds found in the species of family Lamiaceae which have the potential as a drug are very diverse such as eugenol, thymol, Triterpena, ursolic acid, oleanolic acid and micrometric acid, types of terpenoids, alkaloids, flavonoids etc.